Monitoring the Construction Sector in Valle del Cauca - Garay Rodríguez, Seydyss; Vidal-Alejandro, Pavel; Cerón-Ordoñez , Julieth (Apuntes del Cenes, 2023)
The objective of this research is to develop a monthly indicator that synthesizes the economic activity of the construction sector in Valle del Cauca, as a tool for analyzing the production cycle and as a single, public measure that contributes to decision-making. Dynamic factorial models, the Kalman Filter and the Litterman method are used, also used in the Monthly Index of Economic Activity (IMAE), in order to capture signals, changes in the productive cycle of construction and compile the sectoral economic facts that affect production. In the results, the dynamics of the sectoral and economic variables are observed that explain the behavior of the sector in Valle del Cauca, in the period 2009-2020. A change of slope is observed in 2020, as a direct consequence of the crisis generated by Covid-19 and the restrictive measures adopted by the government to contain its advance.